[1938 Campus Map] - Edward R. Wiley::::::author::: (1938)
A comedic campus map included as part of the Sixth Annual Poly Royal brochure. Drawn by Edward R. Wiley, an Air Conditioning student at Poly. The map depicts a number of buildings that were added between 1927 and 1938, including four new residence halls, more engineering and ag facilities, and the President?s House. See the entire program here: https://digital.lib.calpoly.edu/rekl-93365